Self-portraits - Roalf, Peggy (New York : Hyperion Books for Children, 1993)
An exploration of painting through 2000 years of art history, focusing on self-portraits by such artists as Leonardo da Vinci, Rembrandt, Gorky, and Picasso.
"A Jacques Lowe Visual Arts project book"--T.p. verso.
Includes glossary and index.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Library Talk
7.9
Keywords: Self-portraits -- History -- Juvenile literature; Portrait painting -- History -- Juvenile literature; Self-portraits.; Art -- History; Art appreciation; Portrait painting -- History; Art -- History; Art appreciation